2012
DOI: 10.1111/j.1365-2036.2012.05133.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: esomeprazole for the prevention of nonsteroidal anti‐inflammatory drug‐related peptic ulcers in Japanese patients

Abstract: SUMMARY BackgroundThe use of proton pump inhibitors for prevention of nonsteroidal anti-inflammatory drug (NSAID)-induced gastrointestinal adverse events is well documented. However, data regarding the efficacy and safety of this approach in Japan are scarce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Indeed, the ulcer-free rate with esomeprazole 20 mg od in the present 1-year study (95.9%) is better than those seen in the placebo-controlled, 6-month VENUS and PLUTO studies (ulcer-free rates of 94.7% and 94.8%, respectively; life-table estimates) [13]. A double-blind, randomised placebo-controlled trial conducted in Japan also showed superior efficacy of esomeprazole in preventing NSAID-related ulcer recurrence compared with Western studies [14]. …”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Indeed, the ulcer-free rate with esomeprazole 20 mg od in the present 1-year study (95.9%) is better than those seen in the placebo-controlled, 6-month VENUS and PLUTO studies (ulcer-free rates of 94.7% and 94.8%, respectively; life-table estimates) [13]. A double-blind, randomised placebo-controlled trial conducted in Japan also showed superior efficacy of esomeprazole in preventing NSAID-related ulcer recurrence compared with Western studies [14]. …”
Section: Discussionmentioning
confidence: 68%
“…The proton pump inhibitor (PPI) esomeprazole has been shown to be efficacious in the prevention of peptic ulcers and upper GI symptoms related to NSAID use in European, North American and Japanese patients [12-14], but few long-term studies have been conducted in the corresponding Japanese population. The present study therefore investigated the safety and tolerability of long-term treatment with esomeprazole 20 mg in Japanese patients with an endoscopically-confirmed history of peptic ulcer who were also receiving daily NSAID therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, both lansoprazole and esomeprazole significantly reduce the recurrence of peptic ulcers in Japanese patients using NANSAIDs. Furthermore, at present, the use of PPIs to prevent peptic ulcer recurrence in patients using NSAIDs is approved by the Japanese health insurance system in patients using NSAIDs (7,8). The results of our study indicate that PPIs, but not H2RAs, prevent the occurrence of peptic ulcers and hemorrhagic lesions in elderly patients receiving NANSAIDs.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, the effects of PPIs are superior to those of misoprostol in preventing peptic ulcer recurrence in patients taking NSAIDs (6). Although gastric acid secretion is lower in Japanese than in Western populations, both lansoprazole and esomeprazole significantly reduce the recurrence of peptic ulcers compared with mucosal protective agents (MPAs) in NSAID users (7,8). Lansoprazole is also superior to MPAs in reducing the recurrence of peptic ulcers associated with LDA (9).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term administration of proton pump inhibitors (PPIs) is useful for preventing recurrent reflux esophagitis or recurrent gastroduodenal ulcers induced by nonsteroidal anti-inflammatory drugs or low-dose aspirin [1, 2]. However, several adverse reactions, such as an increase in the blood gastrin level, have been reported.…”
Section: Introductionmentioning
confidence: 99%